Peningkatan Kapasitas Administrasi dan Pengelolaan Dana Bergulir Melalui Program Pendampingan pada UPTD Dana Bergulir Dinas Koperasi, UKM, dan Perdagangan Kota Pematangsiantar - Devi Septiana Sitohang; Nancy Nopeline (LPPM Politeknik Piksi Ganesha, 2025)
Revolving fund programs are one of the local government policy instruments aimed at strengthening capital access and business sustainability for Micro, Small, and Medium Enterprises (MSMEs). However, the effectiveness of such programs largely depends on administrative capacity and compliance in fund management and reporting. This community service activity aims to analyze the impact of administrative assistance on improving MSME capacity and the governance quality of revolving funds at the Revolving Fund Unit of the Office of Cooperatives, MSMEs, and Trade of Pematangsiantar City. The methods employed include field observation, direct administrative assistance, documentation, and pre- and post-assistance evaluation. The assistance focused on improving installment payment records, developing administrative databases, and strengthening MSMEs’ understanding of revolving fund reporting procedures. The results indicate that administrative assistance positively impacts financial record orderliness, ease of arrears monitoring, and increased awareness of administrative compliance among MSMEs. This activity demonstrates that administrative assistance plays a strategic role in enhancing the effectiveness of revolving fund programs, strengthening MSME institutional capacity, and supporting transparency and accountability in local public fund management.